Rosa roxburghii Tratt juice ameliorates metabolic disorder in arsenicosis patients based on the analysis of untargeted plasma metabolomics - Yang, Luming; Zhu, Kai; Wang, Wenjuan; Sun, Baofei; Luo, Peng; Zhang, Aihua (Frontiers in Pharmacology, 2025)
Arsenic is an environmental metalloid contaminant known to induce multi-system and multi-organ damage, yet the precise toxicological mechanisms remain unclear. Moreover, effective low-toxicity interventions or treatments are lacking. This study aims to investigate the potential ameliorative effects of Rosa roxburghii Tratt juice (RRTJ) on metabolic disorders in arsenicosis patients, with a focus on plasma metabolite profiles. Using ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS), we analyzed the plasma metabolic profiles of arsenicosis patients before and after RRTJ intervention. After RRTJ intervention, significant alterations were observed in the plasma levels of 61 metabolites, with 30 metabolites upregulated and 31 downregulated. These metabolites were predominantly involved in six key biological pathways, including taurine and hypotaurine metabolism, histidine metabolism, β-alanine metabolism, glycine, serine, and threonine metabolism, pentose and glucuronate interconversions, as well as cysteine and methionine metabolism. In conclusion, RRTJ intervention may effectively alleviate metabolic disorders associated with arsenic toxicity, potentially through its antioxidant, anti-inflammatory effects and regulation of methylation pathways.